Influence of tropical plant sources containing plant secondary compound on rumen fermentation using in vitro gas fermentation technique - NORRAPOKE, THITIMA; WANAPAT, METHA; FOIKLANG, SUBAN (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to investigate the effect of mangosteen peel powder (MPP) and Centella asiatica powder (CAP) supplementation on gas production kinetics and fermentation efficiency using in vitro gas production technique. Two male, rumen fistulated swamp buffaloes were used as rumen fluid donors. The treatments were arranged according to a 3×3 factorial arrangement in a completely randomized design using 3 levels of CAP supplementation (0, 5, 10 mg) and 3 levels of MPP supplementation (0, 5, 10 mg). Untreated rice straw was used as a main roughage source. Under this investigation, the results revealed that supplementation of CAP and MPP showed an effect on gas production kinetics, except for the gas production from the immediately soluble fraction (a), while treatments with combination of CAP and MPP at 5 mg, each resulted in the highest values. Supplementation of either CAP or MPP up to 10 mg reduced the gas production kinetics. In addition, in vitro degradability of DM (IVDMD) and OM (IVOMD) were not affected by CAP or MPP supplementation; however, there was a tendency increase on IVDMD by CAP and MPP supplementation (P=0.08). CAP and MPP supplementation reduced total volatile fatty acid and acetic acid while propionic acid and butyric acid were enhanced especially in treatment combination of CAP and MPP supplementation. Methane production were decreased with increasing level of CAP and MPP supplementation both in combination and separately. On the other hand, ammonia nitrogen (NH3-N) concentration was not influenced by CAP and/or MPP supplementation; except at 4 h incubation, while an increasing of NH3-N concentration was obtained by dietary supplementation. Based on the present findings, it could be concluded that supplementation of CAP and MPP and/or combination could increase gas production kinetics, IVDMD and propionic acid while methane production was suppressed. It is recommended that level of CAP and MPP supplementation was at 5 mg and the combination at ratio of 5 to 5 mg, CAP and MPP. However, in vivo trials should be further conducted to elucidate the effect of CAP and MPP supplementation on rumen ecology as well as ruminant production.